FUNCTIONS AND TASKS OF THE STATE BUDGET (Conferencea, 2024)
The article discusses the current state of the practice of local budget revenue generation in the Republic of Uzbekistan, its problems and new aspects, as well as ways to increase the efficiency of local budget revenue generation based on the goals of an effective tax - budget policy in 2020.